2001
DOI: 10.1046/j.1523-1755.2001.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic renal failure on bone turnover and bone alkaline phosphatase isoforms

Abstract: There are selective differences between the BALP isoforms in CRF compared with healthy adults. The commercial BALP immunoassays are comparable with each other but are unable to distinguish the BALP isoform-specific differences in CRF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
105
3
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 43 publications
9
105
3
1
Order By: Relevance
“…We used instead biochemical markers of bone turnover, but it is unclear to what extent these abnormalities correlate with bone histologic patterns in kidney transplant recipients with or without CKD. Serum CTX is accepted as a marker of bone resorption in patients with normal kidney function (27), but it is unknown to what extent it is diagnostic of histologically defined high turnover bone disease in kidney transplant recipients with or without CKD, especially because levels of CTX are also influenced by kidney function (48). However, we have found similar results when examining other serum markers of bone turnover, such as serum OC levels, an accepted marker of bone formation (28).…”
Section: Discussionsupporting
confidence: 61%
“…We used instead biochemical markers of bone turnover, but it is unclear to what extent these abnormalities correlate with bone histologic patterns in kidney transplant recipients with or without CKD. Serum CTX is accepted as a marker of bone resorption in patients with normal kidney function (27), but it is unknown to what extent it is diagnostic of histologically defined high turnover bone disease in kidney transplant recipients with or without CKD, especially because levels of CTX are also influenced by kidney function (48). However, we have found similar results when examining other serum markers of bone turnover, such as serum OC levels, an accepted marker of bone formation (28).…”
Section: Discussionsupporting
confidence: 61%
“…6 Unlike serum PTH that originates from the parathyroid glands and affects bone metabolism, 3,4,7 serum AlkPhos stems from the bone itself and reflects internal bone activities. 6 Incrementally higher levels of serum AlkPhos can be seen with worsening magnitude of bone turnover.…”
mentioning
confidence: 99%
“…6 Unlike serum PTH that originates from the parathyroid glands and affects bone metabolism, 3,4,7 serum AlkPhos stems from the bone itself and reflects internal bone activities. 6 Incrementally higher levels of serum AlkPhos can be seen with worsening magnitude of bone turnover. 8,9 We recently showed that surrogates of CKD-MBD, including higher serum levels of minerals and higher AlkPhos levels, were associated with increased all-cause death risk in a 2-yr cohort of 58,000 MHD patients.…”
mentioning
confidence: 99%
“…The relationship between higher ALP and fracture could be explained due to high bone turnover [17] and it is recommended to routine measure serum ALP in the treatment of chronic kidney disease-mineral and bone disorder (CKD-MBD) [1]. ALP is primary secreted by the liver and bone, and small amounts are secreted by kidneys, intestine and leukocytes [18].…”
Section: Resultsmentioning
confidence: 99%